2023
DOI: 10.3390/polym15102238
|View full text |Cite
|
Sign up to set email alerts
|

Shear Thickening Fluid and Its Application in Impact Protection: A Review

Abstract: Shear thickening fluid (STF) is a dense colloidal suspension of nanoparticles in a carrier fluid in which the viscosity increases dramatically with a rise in shear rate. Due to the excellent energy absorption and energy dissipation of STF, there is a desire to employ STFs in a variety of impact applications. In this study, a comprehensive review on STFs’ applications is presented. First, several common shear thickening mechanisms are discussed in this paper. The applications of different STF impregnated fabric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 144 publications
1
2
0
Order By: Relevance
“…Note that this was not the highest viscosity value for STF; the experiment was stopped automatically at higher strain rates and the viscosity values were not recorded due to the self-protection of the rheometer from high torque forces. This is the typical curve of a discontinuous shear thickening fluid according to previous reports [2,5]. Hence, it should be concluded that the as-prepared STF will undergo a liquid-solid conversion and then dissipate impact energy under the impact loading.…”
Section: Rheological Behavior Of Stfsupporting
confidence: 76%
See 1 more Smart Citation
“…Note that this was not the highest viscosity value for STF; the experiment was stopped automatically at higher strain rates and the viscosity values were not recorded due to the self-protection of the rheometer from high torque forces. This is the typical curve of a discontinuous shear thickening fluid according to previous reports [2,5]. Hence, it should be concluded that the as-prepared STF will undergo a liquid-solid conversion and then dissipate impact energy under the impact loading.…”
Section: Rheological Behavior Of Stfsupporting
confidence: 76%
“…Shear thickening fluid (STF), as a lightweight, intelligent, and efficient impact protective material, has attracted much research interest [ 1 , 2 ]. It is a solid–liquid suspension system composed ofa high concentration of particles and liquid oligomers.…”
Section: Introductionmentioning
confidence: 99%
“…In cases where fabrics were woven using finer yarns, the friction between individual yarns experienced augmentation subsequent to the impregnation of STF. 15 To ensure a secure deceleration within sandwich composites, the structural configuration must possess the capability to dissipate impact energy while concurrently maintaining the applied impact load within a predetermined threshold. 16 In this context, shear thickening fluid (STF) emerges as a promising avenue to enhance the impact resistance of composite materials, capitalizing on their reversible viscosity transition from lower to elevated levels under the influence of applied stress.…”
Section: Introductionmentioning
confidence: 99%
“…Although, the protection standard of the stab-resistant materials can be achieved by the above preparation methods, and some products also have other functions such as light and flexible, breathable and comfortable, the single-layer original textile still maintains a low level and has unqualified stab resistance [15][16][17][18]. Meanwhile, other problems will also be caused by using the above process, such as instability, heat resistance, softness, thickness, brittleness, and so on [19][20][21]. The difficulty of weaving the stab-resistant material will be reduced, and the convenience of sewing the garment will be improved, if we primarily rely on the matrix textile without adding reinforcement materials.…”
Section: Introductionmentioning
confidence: 99%